The Implementation Of Active Learning In Teaching English At SMPN 3 Kartasura At 2012 / 2013 Academic Year - Prayoga, Indratama Adi, Aryati Prasetyarini, S.Pd, M.Pd, Siti Fatimah, S.Pd, M.Hum (2013)
This research aims at describing English teaching learning process using active learning method at the second semester at SMPN 3 Kartasura at 2012 / 2013 academic year. It is conducted to describe the objective of study, the techniques used in implementation of active learning, the procedure of active learning, the roles of the teacher and the students in the teaching and learning process and the problem faced by the teacher and the students in active learning implementation of SMPN 3 Kartasura. There are three techniques in collecting the data namely: interview, observation and document. The data achieved from information related to the English teaching learning process, script interview and document related to teaching learning process using active learning, script interview and document related to English teaching learning process at SMPN 3 Kartasura. The results of the study show that 1) The techniques used in implementation of active learning. 2) The procedure of active learning. 3) The roles of the teacher in the teaching learning process, 4) The roles of the students in the teaching learning process. 5) The problem faced by the teacher and 6) Problem faced by the students.